DEVELOPMENT OF PROBLEM BASED LEARNING PROBLEM BASED MEDIA PICTURE STORY BOOKS IN LEARNING THEMATIC THEME OF MY OBLIGATIONS AND RIGHTS IN CLASS III OF PRIMARY SCHOOL - Oktavia, Venny; Nurhasanah, Nurhasanah (Media Inovasi Pendidikan dan Publikasi, 2024)
This research is a type of research and development referring to the 4D model consisting of Define, Design, Development and Dissemination. The instrument used to collect data was a questionnaire. Data analysis techniques were descriptive qualitative. The results of the second stage of material expert validation got a percentage of 88%. This percentage included the criteria of